2017
DOI: 10.1155/2017/7823278
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Alcohol Use Disorder: A Meta‐Analysis

Abstract: Empirical research has produced mixed results regarding the effects of acupuncture on the treatment of alcohol use disorder in humans. Few studies have provided a comprehensive review or a systematic overview of the magnitude of the treatment effect of acupuncture on alcoholism. This study investigated the effects of acupuncture on alcohol-related symptoms and behaviors in patients with this disorder. The PubMed database was searched until 23 August 2016, and reference lists from review studies were also revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…In addition, the low-quality evaluation we have included in the study may generate overestimation of the accuracy of diagnosis. Meta-analysis has been a widely used tool in the analysis of clinical cases [ 35 , 36 ]. Along with other mathematical tools [ 37 , 38 ], comprehensive medical analysis can be achieved in future works according to the methods and findings of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the low-quality evaluation we have included in the study may generate overestimation of the accuracy of diagnosis. Meta-analysis has been a widely used tool in the analysis of clinical cases [ 35 , 36 ]. Along with other mathematical tools [ 37 , 38 ], comprehensive medical analysis can be achieved in future works according to the methods and findings of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…While our and other animal studies revealed consistent results that acupuncture suppresses alcohol-related behaviors such as alcohol craving or consumption (13,34), human studies have shown mixed results in the effects of acupuncture on reducing clinical symptoms related to alcohol addiction. For examples, controlled studies showed that severe recidivist alcoholics treated with acupuncture at points specific for the treatment of substance abuse expressed less need for alcohol and less drinking episodes, compared to the control group given acupuncture at nonspecific acupoints (35)(36)(37). However, Worner et al (38) reported negative results of acupuncture treatment on alcoholrelated symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…erefore, nextgeneration sequencing (NGS) of CSF cfDNA will be a better assay to elucidate the relationship between gene mutations and osimertinib efficacy. e above findings can be used for comprehensive analysis in vivo, in vitro, and/or in silico along with other math tools and models, including metaanalysis [25,26], research models [27,28], network pharmacology [29], and molecular docking [30,31].…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 99%